Pengaruh Penggunaan Model Pembelajaran Problem Based Learning terhadap Kemampuan Berfikir Krits Siswa SD/MI - Didit Darmawan; Annisa Maryana (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The ability to think critically is one of the skills that need to be developed from the elementary school level so that students are able to understand, analyze, and solve various problems in learning and daily life. Efforts to build these abilities can be done through the application of a learning model that places students as the center of learning activities, one of which is through Problem Based Learning (PBL). This study aims to describe the effect of the use of the Problem Based Learning model on the critical thinking ability of elementary school students through a literature study approach. Research data was obtained from various scientific journals, previous research results, and reference sources relevant to the topic of discussion. All data were analyzed using qualitative descriptive techniques through the process of collection, reduction, presentation, and drawing conclusions. The results of the study show that the application of Problem Based Learning is able to create a more active learning atmosphere and encourage students to be directly involved in the problem-solving process. In addition to helping students relate material to real situations, this model also contributes to the development of higher-level thinking skills, particularly in discussion activities, group work, and decision-making. Based on these findings, Problem Based Learning can be considered as an effective learning alternative to support the improvement of students' critical thinking skills at the elementary/middle school level.